Analisis Faktor-Faktor Yang Mempengaruhi Pembatalan Pembiayaan Murabahah pada PT. BPRS Puduarta Insani - Cahaya Siagian, Ika Dwi; Rokan, Mustapa Khamal (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Research conducted to analyze the influential factors related to the cancellation of Murabaha financing in Islamic bank PT. Bprs Puduarta Insani is about nonperforming loans, nonconformities in goods, and supporting collateral in Islamic banks. Cancellation of Murabaha financing is often the case that resulted in the cancellation due to nonconformity of the applicable conditions. and at Pt. Bprs Puduarta Insani cancellation of Murabaha financing can be resolved according to the Islamic perspective.